Poetic Justice in Bill Cain's 9 Circles - Ibrahim, Ghassan Awad (International Journal of Humanities and Education Development (IJHED), 2021)
The research paper tackles difficult social problems such as raping and killing especially innocent people due to psychological diseases such as brutality and sadism which lead only to horrific consequences for both wrongdoers and victims. Poetic justice is a significant theme in all genres of literature since readers of any literary work expect that virtue is rewarded and vice is punished or in other words they expect good characters reap the fruit of what they previously sow of good deeds while bad characters deserve their disgraced destiny due to their malignant or bad deeds they have done before. In his masterpiece 9 Circles, Cain shows politics and its ways to impose its negative impact on the behavior of some people, prompting them to do evil attacks against others when he relies on a real story of an American soldier who tortures and kills not only some innocent people but also some animals for enjoyment.